Tetap Pilih Yang Benar Walaupun Sukar: Pembinaan Iman di GPIBI Amanat Agung Kalasan - Epafras Mujono; Rut Melisa (Journal Of Social Empowerment Publications, 2024)
This Community Service activity is motivated by the fact that the lives of Christians are always faced with difficulties and are required to choose the right things according to God's Word in facing them. In order to choose the right thing, Christians often experience struggles, both struggles in choosing and in bearing the consequences or risks of their choices. Therefore, the aim of this activity is: First, to explain the principles that must be adhered to in choosing the right thing, even if it is difficult, both difficult in choosing and difficult in facing the risks of that choice. Second, to measure the level of respondent satisfaction with the material and delivery of the material for this activity. The method used to present this article is the descriptive method, while the method used in the activity is the lecture method. The results of this activity were: There were no (0%) people who said they were dissatisfied, there were no people (0%) who said they were dissatisfied, there were 1.25 people (1.09%) who said they were neutral, there were 78.3 people (66 .2%) said they were satisfied and 33.25 people (32.71%) said they were very satisfied. It can be concluded that the level of satisfaction of the audience or participants in this community service activity is at a high level.